Vanishing Voices: Tracing the Trade Networks and Distribution Pathways of Songbirds in Banda Aceh Markets - Hanif Raihan; Devi Syafrianti; Abdullah Abdullah; Fitrah Asma Ulhusna; Yaumil Istiqlal M. Nur; Cut Nurmaliah; Ismul Huda (Jurnal Penelitian Pendidikan IPA, 2025)
Tracing the trade and distribution pathways refers to the systematic analysis of the origins, movement routes, and distribution patterns of a commodity, such as songbirds, from its source to the final market or end consumer. This study explored the dynamics of bird trade in the markets of Banda Aceh city, focusing on species diversity, conservation status, species origin, and trade patterns. The study was conducted in nine sub-districts, covering 18 bird shops, using a descriptive qualitative approach. Data were collected through direct observation, market surveys, and structured interviews with traders. Species identification was conducted using the Birds of the Indonesian Archipelago guide, while conservation status was evaluated based on the IUCN Red List and CITES Appendices. In addition, Geographic Information System (GIS) software was used to map bird trade distribution channels. The results showed the presence of 54 bird species with a total of 638 individuals, mostly from the Passeriformes order. The most commonly traded species was Acridotheres javanicus (kerak kerbau), with 132 individuals, reflecting its high demand due to its adaptability and affordability. Conservation analysis showed the vulnerability of species such as Gracula religiosa (Nias parrot), which is listed in Appendix II of CITES, and Rubigula dispar (yellow finch), which is categorized as Vulnerable. This research highlights the complex relationship between the local bird trade and conservation efforts, and the importance of stricter regulation and increased public awareness to protect threatened species. The findings make an important contribution to policy recommendations in order to promote sustainable bird trade and biodiversity conservation in Banda Aceh.